Parameters for Change in Offline Gambling Behavior After the First COVID-19 Lockdown in Germany - Kalke, Jens; Schütze, Christian; Lahusen, Harald; Buth, Sven (Frontiers in Psychology, 2022)
NEW ABSTRACT!!! Introduction: In spring 2020, the first nationwide lockdown in response to the spreading COVID-19 pandemic came into effect in Germany. From March to May, gambling venues, casinos, and betting offices were forced to close. This study explores how land-based gamblers respond to short-term closures of higher-risk forms of gambling. Which gamblers are particularly susceptible to switching to online gambling? Which are more likely to use the lockdown as an opportunity to quit or pause gambling? Potential parameters for these switching or cessation processes are identified using multivariate multinomial logistic regression analysis. Methods: The research questions are analyzed on the basis of quantitative data. For this purpose, a survey was conducted among members of a comparatively large German online access panel (‘PAYBACK panel’). The sample of analysis consisted of 612 gamblers who had participated in at least one higher-risk form of gambling and had done so exclusively offline before the first lockdown (January & February 2020). Results: 37.1% of sports bettors ceased participation in higher-risk forms of gambling, compared to 64.1% of casino gamblers. Switching to online gambling, on the other hand, was a rather rare event, regardless of the form of gambling: the proportions differ between 7.7% (slot machines) and 10.9% (sports betting). In the multivariate model female gender, younger age and a lower frequency of gambling before the first lockdown were found to be significant factors for quitting (instead of continuing) higher-risk offline gambling forms. Secondly, the analysis revealed that individuals with more pronounced cognitive distortions had an increased risk of switching to online gambling rather than staying offline. Discussion: A key finding of this study is that the temporary closure of offline venues does not result in a significant shift towards the online market. Instead, the results of this study show that these short, temporary closures of gambling venues were an appropriate opportunity to give individual groups of gamblers the opportunity to reflect, reduce, or quit their gambling behavior. It is worth considering implementing such temporary closures as a preventive measure in the future - this should be investigated in advance in further evaluation studies.